1997
DOI: 10.1182/blood.v90.12.4979
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of Ferritin by Rat Hepatoma Cells and Its Regulation by Inflammatory Cytokines and Iron

Abstract: The possibility that serum ferritin is a secreted protein and an acute phase reactant regulated by inflammatory hormones and iron was examined in a hepatic cell line that secretes plasma proteins. Differentiated rat hepatoma cells released albumin and ferritin into the medium, as determined by rocket immunoelectrophoresis and isolation of ferritin by standard procedures plus immunoaffinity chromatography, following labeling with radioactive amino acid. Administration of interleukin-1–β (IL-1) or tumor necrosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
94
0
5

Year Published

1999
1999
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(101 citation statements)
references
References 35 publications
2
94
0
5
Order By: Relevance
“…In particular, it has been hypothesized that during an ongoing infection, the signaling mediated by bacterial/viral CpG DNA and TLR9 could activate the inflammasome, leading to IL-1 and IL-18 production [18][19][20]. Through DAMP signaling, infection could also increase the production of hemoglobin [21] and activate macrophages, which are prominent producers of ferritin [22,23], amplifying the inflammatory loop [23]. Moreover, a correlation between the serum levels of CD163, a marker of macrophage activation [24], and ferritin in patients with MAS has been reported [25].…”
Section: Sars-cov-2 Infection and The Pathophysiology Of Cytokine Relmentioning
confidence: 99%
“…In particular, it has been hypothesized that during an ongoing infection, the signaling mediated by bacterial/viral CpG DNA and TLR9 could activate the inflammasome, leading to IL-1 and IL-18 production [18][19][20]. Through DAMP signaling, infection could also increase the production of hemoglobin [21] and activate macrophages, which are prominent producers of ferritin [22,23], amplifying the inflammatory loop [23]. Moreover, a correlation between the serum levels of CD163, a marker of macrophage activation [24], and ferritin in patients with MAS has been reported [25].…”
Section: Sars-cov-2 Infection and The Pathophysiology Of Cytokine Relmentioning
confidence: 99%
“…Small amount of ferritin are present in the blood and consist of ferritin L, a glycosylated form of L termed ferritin G, and trace amounts of ferritin H . It is mainly secreted from macrophages, by hepatocytes, and lymphoid cells, but most aspects of its secretion remain unknown. Serum ferritin has a wide clinical utility primarily as an indicator of intracellular iron stores .…”
Section: Introductionmentioning
confidence: 99%
“…These data suggest that the role of Fpn1 in hepatocytes might not be as important as it is in duodenal enterocytes or macrophages. Moreover, several studies have shown that hepatocytes can secrete the iron storage protein, ferritin, a process that can be enhanced by iron stimulation 22, 23. Hepatocytes also express high levels of the heme transporter, feline leukemia virus subgroup C receptor 24.…”
mentioning
confidence: 99%